Peningkatan Keterampilan Membaca pada Siswa Kelas 2 SDN 02 Karangasem Talun Berbasis E-COMIC - Nasrudin Nasrudin (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Reading skills are very important skills taught to students. In the school curriculum, reading skills are taught to students in grades 1 and 2 of elementary school. The 2003 National Education System Law in Chapter III article 4 paragraph 4 concerning the Principles of Education Implementation states that education is held by developing a culture of reading, writing, and arithmetic for all members of the community. For this reason, the purpose of this study is to improve reading skills in grade 2 students of SDN 02 Karangasem Talun based on E-Comic in the odd semester of the 2020/2021 academic year. The subjects in this study were all 2nd-grade students of SDN 02 Karangasem Talun, totaling 21 students. This type of research is Classroom Action Research with four stages following the Kemmis and Mc Taggart model. Data collection techniques using observation, documentation, interviews, and tests. The success indicator in this study is for individual learning completeness if the proportion of students' correct answers is more than the predetermined KKM and for classical learning completeness if at least 85% of all students have reached the KKM. The results of this study indicate that in cycles 1 and 2 the average success indicators are 76.19% and 85.71%, so there is no need to continue for cycle 3. For the average class, in cycles 1 and 2 each is equal to 77.50 and 86.25.